2019
DOI: 10.1111/lang.12351
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Instruction and Out‐of‐School Exposure to Foreign Language Input on Learners’ Vocabulary Knowledge in Two Languages

Abstract: This cross-sectional study investigated the impact of length of instruction, out-of-school exposure to foreign language input, and gender on learners' receptive vocabulary knowledge in two foreign languages: French (first foreign language) and English (second foreign language). The findings suggest that, although length of instruction correlated positively with vocabulary knowledge in English and French, the gains remained modest when out-of-school exposure to the foreign language input was limited. Despite fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 65 publications
(95 citation statements)
references
References 53 publications
4
79
0
1
Order By: Relevance
“…Audiovisual input has three advantages compared to written and spoken input: (1) it is motivating, (2) it contains visual support, and (3) it recycles low‐frequency words. First, research into the effects of out‐of‐school exposure on vocabulary learning has shown that learners of different age groups engage more frequently in English‐language TV viewing than in reading English books (e.g., Peters, ; Peters et al, ). As pointed out before, learners are motivated to learn a language through watching TV and movies (Colwell & Ipince Braschi, 2006, as cited in Webb & Rodgers, ; Sockett & Kusyk, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Audiovisual input has three advantages compared to written and spoken input: (1) it is motivating, (2) it contains visual support, and (3) it recycles low‐frequency words. First, research into the effects of out‐of‐school exposure on vocabulary learning has shown that learners of different age groups engage more frequently in English‐language TV viewing than in reading English books (e.g., Peters, ; Peters et al, ). As pointed out before, learners are motivated to learn a language through watching TV and movies (Colwell & Ipince Braschi, 2006, as cited in Webb & Rodgers, ; Sockett & Kusyk, ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it should be noted that Flanders uses L1 subtitles (not dubbing) to make foreign language TV programs and movies accessible, so the participants were used to watching subtitled English‐language TV (see also Peters, ). In addition to L1 subtitles, Flemish EFL learners frequently watch English‐language TV with captions or without subtitles (Peters, ; Peters et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings emerging from these studies have shown that learners of English as a foreign language (i.e., those learners acquiring English in contexts where English is not spoken outside the classroom) are regularly exposed to English language audiovisual input (TV shows, movies), songs, and computer games outside of the classroom, at least in European countries like Denmark, Sweden, and Flanders (Belgium). Despite the growing body of evidence for the positive effect of extramural English on learners’ vocabulary knowledge (De Wilde et al., ; Peters, ; Peters, Noreillie, Heylen, Bulté, & Desmet, ; Sundqvist & Wikström, ; Sylvén & Sundqvist, ), research has not yet addressed the question of which words are more likely to be picked up from extramural English. Further, most studies of extramural English have focused on instructed English foreign language (EFL) learners and on vocabulary knowledge at the level of meaning recognition (see Kuppens, , for an exception).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that in instructed settings where the amount of contact with the foreign language is limited vocabulary learning gains are typically small (Peters et al., ; Webb & Chang, ). Researchers (e.g., Peters et al., ; Webb, ) have therefore advocated extramural activities as a way of enhancing learners’ vocabulary gains because of their potential for incidental learning.…”
Section: Introductionmentioning
confidence: 99%